A Pilot Study on the Analysis of Circulating miRNA Upregulation in Laryngeal Cancer - Pintea, Crina Oana; Pricop, Marius; Seclaman, Edward; Balica, Nicolae Constantin; Guran, Kristine; Horhat, Delia Ioana; Mot, Cristian Ion (Diseases, 2025)
Background and Objectives: Laryngeal cancer poses a significant clinical challenge, with late-stage diagnosis contributing to high morbidity and mortality. Circulating microRNAs (miRNAs) represent promising, minimally invasive biomarkers for earlier detection and improved therapeutic monitoring. This pilot study focused exclusively on miRNAs found to be upregulated in laryngeal carcinoma patients, aiming to elucidate their diagnostic and prognostic relevance. Methods: A total of 50 participants meeting standardized inclusion criteria were recruited from the ENT Clinic in Timișoara. Of these, 30 patients provided paired blood samples before and after treatment (surgical or non-surgical). Samples were pooled into three preoperative groups (P1, P2, P3) and three corresponding postoperative groups (C1, C2, C3). miRNAs were extracted from plasma and exosomes, and relative expression was measured by qPCR (Qiagen platform). Statistical analyses included Mann–Whitney U tests, receiver operating characteristic (ROC) curves, and logistic regression. Results: Seven miRNAs consistently exhibited significant upregulation preoperatively. Notably, hsa-miR-424-5p displayed a mean fold change of 4.59 (p = 0.0091) relative to postoperative samples, while hsa-miR-186-5p increased by 2.19-fold (p = 0.0030). hsa-miR-15b-5p also showed a substantial preoperative upregulation of 1.77-fold (p = 0.0057). In ROC analyses, hsa-miR-424-5p yielded an area under the curve (AUC) of 0.82 (95% CI 0.70–0.94), with 78% sensitivity and 80% specificity in distinguishing preoperative from postoperative status. Logistic regression indicated that elevated levels of hsa-miR-424-5p (OR = 1.56, 95% CI 1.10–2.20) and hsa-miR-186-5p (OR = 1.32, 95% CI 1.02–1.68) significantly predicted the preoperative disease state. Conclusions: These data underscore the potential of upregulated circulating miRNAs to serve as biomarkers for active laryngeal cancer and to monitor treatment response. Although preliminary, the findings encourage further research with larger cohorts and additional endpoints. With thorough validation, upregulated miRNAs could be integrated into clinical workflows, enhancing diagnostic precision, risk stratification, and postoperative surveillance in laryngeal cancer.